Immunogenicity to COVID-19 mRNA vaccine third dose in people living with HIV - Alessandra Vergori; Alessandro Cozzi Lepri; Stefania Cicalini; Giulia Matusali; Veronica Bordoni; Simone Lanini; Silvia Meschi; Roberta Iannazzo; Valentina Mazzotta; Francesca Colavita; Ilaria Mastrorosa; Eleonora Cimini; et al. (Nature Communications, 2022)
HIV infection may affect the immune response to vaccination. Here the authors show that humoral response in persons living with HIV after the third dose of a SARS-CoV-2 vaccine is strong and higher than that achieved with the second dose, while cell-mediated immunity remains stable.